Caracterização físico-química, composição e capacidade antioxidante do óleo essencial de Myrcia amazonica DC. (Myrtaceae) - CALAO, Vítor Yesid Pérez (Universidade Federal do Oeste do Pará, 2021)
In the Amazon region exists a big variety of aromatic and medicinal plants that present a high economic potential, but there are few that have been explored commercially. The physicochemical and pharmacological study obtained of vegetal species can drive us to the finding of substances of interest for the man. In this research was conducted the physicochemical study and the antioxidant activity of essential oil of the leaves of Myrcia amazonica DC., (native specie of the region). It was obtained by the hydrodistillation (HD) method the essential oil used for the compounds identification, the physicochemical essays and the antioxidant activity. The essential oil’s chemical composition and the volatile compounds found in the flowers were identified by GCMS. The antioxidant activity was calculated by the ABTS+. and the ORAC methods. There were found majority compounds of interest in the composition of essential oil like the Germacrene D (10,09-16,56%), Germacrene B (9,59-11,09%) and 1-Epi- Cubenol (14,72-20,22%). The yield of the essential oil was between the (0,65-0,96%) for fresh leaves and dry respectively, the difference in the composition of the essential oil both dry leaves and fresh leaves was revelant, the highest value for the antioxidant activity of essential oil was recorded with the ORAC (1310 ± 11 μmol Trolox®/g substance) method compared to the ABTS+. (290 ± 7 μmol Trolox®/g substance) method.